The impact of occupational accidents on operating costs and occupational health and safety costs on the number of occupational accidents - an application in the aviation sector - Topcu, Muhammet Bayram; Gul, Muhammet; Guneri, Ali Fuat (TAYLOR & FRANCIS LTD, 2025)
This article examines the dual effects of occupational health and safety cost (OHSC) fluctuations due to the occupational accident number (OAN), and the impact of the OAN on operating period costs (OPCs). Initially, OHSCs, OANS and other operational data from the company were compiled to build a foundational infrastructure. Subsequently, econometric analysis using regression techniques was conducted to identify relationships between OHSCs and OANs, and between OHSCs and OPCs. Findings suggest that a 1% increase in OAN correlates with a 0.18% rise in OPC, while a 1% increase in OHSC corresponds to a 0.26% increase in OAN. The study also indicates that effective OHSCs can lead to a reduction in OAN, and without the expenditure of OHSCs in the relevant period, the likelihood of OANs occurring increases by approximately 84 times. These insights underscore the critical role of OHSCs in managing operational risks and enhancing performance.
Keywords: occupational health and safety; occupational health and safety costs; occupational accidents; regression analysis; operating costs; INJURIES; Engineering; Public, Environmental & Occupational Health